Teacher Performance Analysis Based on Competency and Work Motivation (A Case Study of Teachers at SD Islam Terpadu Insan Kamil Cimahi) - Iqbal Masduki; Mochamad Vrans Romi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Teacher performance is an important factor in determining the success of the educational process. However, based on the results of interviews at SD Islam Terpadu Insan Kamil Cimahi, several obstacles were still found, such as the lack of teacher performance assessment and the lack of optimal integration of the Independent Curriculum with the integrated Islamic curriculum. Therefore, competence and work motivation need to be considered to support the improvement of teacher performance. This study aims to analyze competence, work motivation, teacher performance, as well as the role of competence and work motivation in improving teacher performance at SD Islam Terpadu Insan Kamil Cimahi.  This study uses a qualitative method with data collection techniques in the form of interviews, observations, and documentation. The research informants consisted of 1 principal and 6 teachers, while the validity of the data was tested through triangulation of sources, techniques, and theories.  The results of the study show that teachers' competence and work motivation are in the good category. Competence is reflected in the aspects of knowledge, understanding, skills, attitudes, and interests, while work motivation is seen from the spirit of achievement, responsibility, recognition, and development of one's potential. Teacher performance is also in the good category based on aspects of work quality, work quantity, punctuality, initiative, and independence. This study concludes that competence and work motivation play an important role in improving teacher performance so that the implementation of learning tasks can take place more optimally.